ASSESSMENT OF VARIABILITY FOR GRAIN YIELD AND QUALITY CHARACTERS IN RICE (Oryza sativa L.) - T. SRINIVAS, S.K. SAMEERA, A. PRASANNA RAJESH, V. JAYALAKSHMI, P.J. NIRMALA and (The Journal of Research, PJTSAU, 2017)
India has the largest area under rice in the world and ranks second in production. Therefore, intensive efforts are needed to improve grain yield and quality in rice. In this context, critical assessment of the nature and magnitude of genetic variabilitypresent for grain quality characters in addition to yield is one of the pre-requisites in formulation of effective breeding strategies aimed at improvement of yieldand quality. Hence, in the present investigation, attempts have been made to estimate genetic variability for various grain quality characters besides grain yield.